2010
DOI: 10.1002/mame.200900347
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Nickel/Titanium Alloy and Titanium Surfaces via a Polyelectrolyte Multilayer/Calcium Phosphate Hybrid Coating

Abstract: The report shows that simple LbL deposition of positively charged chitosan and negatively charged heparin can be used to efficiently modify the native surface of both NiTi and Ti without any previous treatments. Moreover, mineralization of the polymer multilayers with calcium phosphate leads to surfaces with low contact angles around 70 and 20° for NiTi and Ti, respectively. This suggests that a polymer multilayer/calcium phosphate hybrid coating could be useful for making NiTi or Ti implants that are at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 68 publications
1
23
1
Order By: Relevance
“…In summary, the study shows that calcium phosphate formation beneath polycationic monolayers is significantly different from calcium phosphate formation on polymer multilayers on solid substrates 18, 20–22. Earlier studies either show the formation of small, rather dense particles or very large fluffy aggregates.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…In summary, the study shows that calcium phosphate formation beneath polycationic monolayers is significantly different from calcium phosphate formation on polymer multilayers on solid substrates 18, 20–22. Earlier studies either show the formation of small, rather dense particles or very large fluffy aggregates.…”
Section: Resultsmentioning
confidence: 65%
“…The unique feature of the current study is indeed that the effect of polycations at the air–water interface is for the first time evaluated at different pH values, including non‐physiological conditions. Open questions, therefore, concern the role of the pH on calcium phosphate mineralization on polymer films such as those just discussed 18, 20–22, 24. Unfortunately there are no data available on this topic at the moment, yet our work suggests that the degree of charging, also in polycations, is a key influence in calcium phosphate formation.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Schweizer, et al prepared hybrid films from chitosan/heparin multilayers and calcium phosphate and demonstrated that the specific composition of these hybrid films strongly affects their water contact angle [16]. Fratzl and coworkers used a coprecipitation process for the synthesis of chitosan-based hybrids [17].…”
Section: Introductionmentioning
confidence: 99%